The vestibular approach in transoral thyroid surgery: proceedings within the clinical setting - Karakas, Elias (Translational Cancer Research, 2017)
Since the first reports regarding natural orifice transluminal endoscopic surgery (NOTES) via so-called natural orifices more than 10 years ago, several techniques have more or less successful been implemented in different surgical fields. Aim of the NOTES procedures is to minimize operative trauma and optimize cosmetic results. Different study groups attempted to find a transoral access to the thyroid region, considering the embryologic origin of the thyroid and parathyroid glands.